Congenital Granular Cell Epulis: A Case Report - Rekha Narendra Patil; Satish Helwatkar; Waman Raut (Journal of Medical Sciences and Health, 2017)
Congenital granular cell epulis (CGCE) is a rare benign lesion of the newborn. It was first described in 1871 by Neumann. The exact etiology of the condition still remains unknown. There is marked female preponderance 10:1. The lesion is usually solitary, but multiple lesions are seen in 10% of cases. They arise from the gingival mucosa of the maxillary or mandibular alveolar ridge. Depending on the size of the lesion it can be asymptomatic or can cause feeding or respiratory problems. Imaging studies can help in the prenatal diagnosis of the lesion as early as 26 weeks of pregnancy. Spontaneous regression can occur, but surgery is the treatment of choice in symptomatic patients. CGCE is important as it has to be differentiated from the other aggressive lesions of early life. We report a case of 1 day old female neonate with intraoral lesion. The histopathology of the excised specimen helped in the diagnosis.